Considering choline as methionine precursor, lipoproteins transporter, hepatic promoter and antioxidant agent in dairy cows. (December 2017) - Abbasi, Imtiaz; Abbasi, Farzana; Soomro, Rab; Abd El-Hack, Mohamed; Abdel-Latif, Mervat; Li, Wen; Hao, Ren; Sun, Feifei; Bodinga, Bello; Hayat, Khawar; Yao, Junhu; Cao, Yangchun
Abstract During the transition period, fatty liver syndrome may be caused in cows undergo negative energy balance, ketosis or hypocalcemia, retained placenta or mastitis problems. During the transition stage, movement of non-esterified fatty acids (NEFA) increases into blood which declines the hepatic metabolism or reproduction and consequently, lactation performance of dairy cows deteriorates. Most of studies documented that, choline is an essential nutrient which plays a key role to decrease fatty liver, NEFA proportion, improve synthesis of phosphatidylcholine, maintain lactation or physiological function and work as anti-oxidant in the transition period of dairy cows. Also, it has a role in the regulation of homocysteine absorption through betaine metabolite which significantly improves plasma α-tocopherol and interaction among choline, methionine and vitamin E. Many studies reported that, supplementation of rumen protected form of choline during transition time is a sustainable method as rumen protected choline (RPC) perform diverse functions like, increase glucose level or energy balance, fertility or milk production, methyl group metabolism, or signaling of cell methionine expansion or methylation reactions, neurotransmitter synthesis or betaine methylation, increase transport of lipids or lipoproteins efficiency and reduce NEFA or triacylglycerol, clinical or sub clinical mastitis and general morbidity in the transition dairy cows. The purpose of this review is that to elucidate the choline importance and functions in the transition period of dairy cows and deal all morbidity during transition or lactation period. Furthermore, further work is needed to conduct more studies on RPC requirements in dairy cows ration under different feeding conditions and also to elucidate the genetic and molecular mechanisms of choline in ruminants industry.